Clinical, Biochemical, and Molecular Characterization of Neonatal-Onset Dubin–Johnson Syndrome in a Large Case Series From the Arabs - Al-Hussaini, Abdulrahman; AlSaleem, Badr; AlHomaidani, Hamad; Asery, Ali; Alruwaithi, Muhanad; Alameer, Mohammed; Afashah, Waleed; Salman, Bashir Muhammed; Almontashiri, Naif (Frontiers in Pediatrics, 2021)
Background: There are only few case reports and small case series on neonatal-onset Dubin-Johnson syndrome (DJS), particularly from Far-East Asia, Iranian and Moroccan Jews, and Europe. Objectives: In this first study from Arabs and the largest series reported to date, we characterized the clinical, laboratory, and molecular features and outcome of gene-confirmed neonatal-onset DJS. Methods: We reviewed our database of 533 cases of neonatal cholestasis that presented to our center during the period from 2008 until 2019. We identified neonates with a disease-causing mutation in ABCC2 gene. Results: Twenty-eight neonates with DJS were diagnosed (5.3%). All of the 28 were full-term, well looking neonates without hepatosplenomegaly, with cholestasis and normal liver synthetic function since the first week of life that resolved within 3 to 6 months of age, followed by a benign course punctuated by recurrent episodes of jaundice in 43% during a median follow up period of 9.25 (range 2.5 – 14 years). Alanine aminotransferase levels were within normal range in 26 patients (92%) and mildly elevated in 2 patients. ALT levels were significantly lower in neonates with DJS than in other cases with neonatal cholestasis from other causes (P < 0.001). The median urinary coproporphyrin I % was 88% (IQ1-IQ3 = 84.2% - 92.7%). We identified 4 homozygous variants in the ABCC2 gene (from 22 unrelated families), one splicing variant (c.3258+1G>A; p.?) and 3 were missense variants; two of which were novel missense variants [c.1594G>A (p.Glu532Lys); c.2439G>C (p.Lys813Asn)]. The p.Gly758Val mutation has occurred in 23 patients (from 19 unrelated families). Conclusions: Our study suggests that normal ALT-cholestasis in a well-looking neonate should trigger evaluation for DJS. The p.Gly758Val variant in ABCC2 is the most predominant mutation among Arabs with “founder effects”. These findings are likely to inform and guide the clinical and molecular diagnoses of the neonatal-onset DJS through the established ABCC2 variant spectrum in this population.